The chronicles of Narnia- Prince Caspian - Lewis, C.S; Baynes,Pauline (London Harper Collins Childrens Book, 2008)
Caspian's father is dead, and Narnia is ruled by his wicked uncle Miraz. Hearing tales of the old Narnia and of Talking Beasts from his tutor, a dwarf, Caspian escapes from the palace to find it